2006
DOI: 10.1002/pssa.200521419
|View full text |Cite
|
Sign up to set email alerts
|

Single‐crystal nanorings of β‐gallium oxide synthesized using a microwave plasma

Abstract: In this study, a new method for synthesizing single‐crystal ring‐like β‐Ga2O3 nanobelts (here named nanorings), of only 0.2–1 µm in diameter, is presented. A microwave plasma method involving liquid‐phase gallium containing H2O in an Ar atmosphere, using silicon as the substrate, is used for the first time. The morphology and structure of the nanorings were analysed using scanning electron microscopy and X‐ray diffraction. The morphology of β‐Ga2O3 nanobelts was also characterized using transmission electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…12À17 Recently, nanorings/springs/helical structures for a number of inorganic materials such as CuO, 18 SnO 2 , 19 InGaN, 20 R-Ga 2 O 3 , 21 InP nanosprings, 22 PbSe, 23 BN, 24 AlN, 25 ZnO, 26À29 gold, 30 Zn 2 SnO 4 , 31 amorphous SiO 2 , 32 SiC nanosprings, 33 and carbon nanotube coils 34 have been reported. To the best of our knowledge, (NH 4 ) 0.5 V 2 O 5 3 mH 2 O ring/triangle and oval forms have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…12À17 Recently, nanorings/springs/helical structures for a number of inorganic materials such as CuO, 18 SnO 2 , 19 InGaN, 20 R-Ga 2 O 3 , 21 InP nanosprings, 22 PbSe, 23 BN, 24 AlN, 25 ZnO, 26À29 gold, 30 Zn 2 SnO 4 , 31 amorphous SiO 2 , 32 SiC nanosprings, 33 and carbon nanotube coils 34 have been reported. To the best of our knowledge, (NH 4 ) 0.5 V 2 O 5 3 mH 2 O ring/triangle and oval forms have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is demonstrated that smooth β‐Ga 2 O 3 nanowires have been synthesized by conventional vapor–liquid–solid growth technique 6, 13. However, if the shapes and/or dimensions of the nanowires or nanobelts can be controlled as designed, the structural modification technique would open wide range of applications, especially for optoelectronic or photonic applications 14–18. One of the techniques to control the shape and dimension is considered to be modification of the surface energy by incorporation of additional elements 19–21.…”
Section: Introductionmentioning
confidence: 99%
“…One of the techniques to control the shape and dimension is considered to be modification of the surface energy by incorporation of additional elements 19–21. Another method for the structural control is the growth direction control induced by the defect formation 17, 22.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing attention is being nowadays paid to ring [27][28][29][30][31][32] like nanomaterials because of their size, special morphology-related properties and potential nanoscale applications [31]. This paper reports on the synthesis and the electrochemical performance of V2O5 nanorings and Na0.3V2O5 nanoribbons obtained under hydrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%